Amandemen Lembaga Legislatif dan Eksekutif: Prospek dan Tantangan - Saldi Isra (Universitas Islam Indonesia, 2003)
The constitutional amendments for UUD 1945 gives a new opportunity and also challenge for all. This can be seen as